No Consequence for Lateral View X-Ray in Displaced Proximal Femoral Fractures in the Elderly - Macke, Christian; Werner, Maic; Herold, Lambert; Krause, Olaf; Graulich, Tilmann; Clausen, Jan-Dierk; Krettek, Christian; Liodakis, Emmanouil (Frontiers in Surgery, 2021)
Background: Due to demographic changes, proximal femoral fractures (PFF) in the elderly rise constantly. The standard diagnostic tool is still the X-ray of the pelvis/hip in two planes. Our hypothesis was that the lateral-view X-ray has little influence on classification, planning of the operative procedure, and choice of implant in geriatric patients. Methods: Retrospective analysis of all initial X-rays of PFF in geriatric patients (≥70 years) from May 2018 until August 2019 in a Level I Trauma center. Three experienced consultants categorized the fractures on the ap pelvis view and performed Garden and Pauwels classification as well as a two-staged classification displaced/nondisplaced [for femoral neck fractures (FNF)] or AO Classification [for intertrochanteric fractures (ITF)]. Afterward, they decided the operative strategy as well as implant choice [dynamic hip screw (DHS), intramedullary nail (IMN), or arthroplasty]. After 4 weeks, they categorized all fractures again with now available lateral view X-rays in a different order. Results: Two hundred seven patients (146 female, 61 male; 70.5 vs. 29.5%) with 90 FNF and 117 ITF (43.5 vs. 56.5%) could be included. Age was 84.6 ± 6.9 years. The treatment was in 45 cases DHS, in 82 cases IMN, and for the other 80 cases arthroplasty. The interobserver reliability of the classifications were poor, except for the two-staged classification [Fleiss-κ ap view only = 0.708 (CI 95% 0.604, 0.812) vs. additional lateral = 0.756 (CI 95% 0.644, 0.869)]. Moreover, independent from the classification, there were no significant changes in management and choice of implant with additional lateral view. Conclusions: Regarding our results, we consider the lateral view dispensable for standard X-ray of displaced PFF in geriatric patients. In nondisplaced fractures, it could be added secondary.